(untitled) (Andamios, Revista de Investigación Social, 2026)
This article, the result of research with young women in three regions of Mexico –northwest, west, and central–, shows how the emotional experience of pain linked to events of violence can be approached through sensory ethnography. It develops a proposal for photo-elicitation, a photographic intervention of family albums, taking into account that the body is the vehicle through which we experience and interpret life. The interpretive phenomenological analysis is carried out in three sections: epiphany, contingency, and emotional emergence. Some similarities in the themes presented are both interesting and troubling. This allows us to observe that the intervened and analyzed photographic images become a reflection not only on the people who create them but also on the society that produces them.